Toner for electrostatic charge image development
The toner formulation, featuring a crystalline polyester resin and a controlled amount of ester waxes, addresses the challenges of smear properties and durability in existing toners, achieving superior performance in both aspects.
Patent Information
- Application Number
- JP2024166489
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-11
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-23
AI Technical Summary
Existing toners face challenges in achieving both smear properties and durability due to the bleeding of release agents, which affects adhesion to the fixing roller and smear resistance, and the use of ester wax, which can lead to insufficient smearing and durability issues.
A toner formulation that includes a crystalline polyester resin with a controlled ester group concentration and two types of ester waxes, where the total content of the ester wax is between 1 and 10 parts by mass, ensuring optimal smearing and durability without excessive wax accumulation.
The toner exhibits excellent smearability and durability, maintaining adhesion to the fixing roller and providing effective smear resistance without compromising on durability, as evidenced by improved performance in both smearability tests and durability assessments.
Smart Images

Figure 2025066655000001 
Figure 2025066655000002 
Figure 2025066655000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing electrostatic images used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]
[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of toners for developing electrostatic images (hereinafter, simply referred to as "toners") that can handle higher image quality and faster speeds. For example, as the machine speed increases, the amount of heat applied to the toner applied to the recording paper during fixing decreases, so there is a demand for toners with better low-temperature fixing properties.
[0003] Therefore, as a binder resin for toner, it is known that a crystalline polyester resin is effective in improving the low-temperature fixing property of the toner, and its combined use with an amorphous polyester resin is being considered. Furthermore, from the viewpoint of improving the fixing property in the high-temperature range, various release agents are also being considered (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-109704 A [Patent Document 2] JP 2013-142712 A [Patent Document 3] International Publication No. 2017 / 179357 Summary of the Invention [Problem to be solved by the invention]
[0005] The release agent bleeds out onto the toner surface when the toner is thermally fixed, suppressing the adhesion of the toner to the fixing roller, and its presence on the surface of the fixed image imparts smear resistance (abrasion resistance of the printed matter). However, since the ester wax commonly used as a toner release agent becomes less viscous when melted, a small amount of the wax tends to leave little residue on the printed matter surface, resulting in insufficient smear resistance. On the other hand, by increasing the amount of ester wax, smear resistance is improved, but the increased amount of wax on the toner surface makes filming on the developing blade more likely to occur in the developing process, and durability is deteriorated (white streaks occur when printing a solid black image). Therefore, it is difficult to achieve both smear resistance and durability.
[0006] The present invention relates to a toner for developing electrostatic images which is excellent in both smear resistance and durability. [Means for solving the problem]
[0007] The present invention relates to a toner for developing electrostatic images, comprising a crystalline polyester resin C, an amorphous polyester resin A, and a release agent, wherein the crystalline polyester resin C is a polycondensate of an alcohol component and a carboxylic acid component, the alcohol component contains ethylene glycol and / or the carboxylic acid component contains an α,ω-dicarboxylic acid compound having 4 carbon atoms, the ester group concentration of the crystalline polyester resin C is 5.5 mmol / g or more and 9.0 mmol / g or less, and the release agent contains two types of ester waxes, the total content of the ester waxes being 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the total amount of the crystalline polyester resin C and the amorphous polyester resin A. Effect of the Invention
[0008] The toner for developing electrostatic images of the present invention exhibits excellent effects in terms of smear resistance and durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The toner for developing electrostatic images of the present invention is characterized by using a specific raw material monomer, containing a crystalline polyester resin with a controlled ester group concentration, and two types of ester wax. The reason why the toner for developing electrostatic images of the present invention can achieve both smear resistance and durability is not clear, but is presumed to be as follows. Note that the following mechanism is presumed and is not limited thereto.
[0010] In the present invention, by using two kinds of ester waxes in combination, the two are mixed together and the crystallinity of the wax itself is moderately weakened. At the same time, by using crystalline polyester resin C with a large amount of ester groups and a structure in which the ester groups are partially close to each other, the interaction between the ester wax and the ester groups is strengthened, and the ester wax is prevented from excessively migrating to the fixing roller side during thermal fixing, and is more likely to remain on the toner surface. As a result, it is believed that it is possible to achieve both the durability of the toner and the smear resistance of the printed matter without excessively increasing the amount of release agent.
[0011] The toner of the present invention contains a crystalline polyester resin C, an amorphous polyester resin A, and a release agent.
[0012] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, that is, the value of [softening point / maximum endothermic peak temperature]. The crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. On the other hand, an amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the resin has a crystallinity index of more than 1.4, preferably more than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.
[0013] Crystalline polyester resin C is a polycondensate of an alcohol component and a carboxylic acid component, the alcohol component containing ethylene glycol and / or the carboxylic acid component containing an α,ω-dicarboxylic acid compound having 4 carbon atoms, and has a predetermined ester group concentration.
[0014] The ester group concentration of crystalline polyester resin C is 5.5 mmol / g or more, preferably 6.0 mmol / g or more, more preferably 6.5 mmol / g or more, even more preferably 6.7 mmol / g or more, and is 9.0 mmol / g or less, preferably 8.0 mmol / g or less, more preferably 7.5 mmol / g or less, even more preferably 7.0 mmol / g or less.
[0015] In the present invention, the ester group concentration of the polyester resin is calculated from the following formula.
[0016]
number
[0017] (In the formula, A is the total amount (mol) of ester bonds produced when all the raw material monomers of the polyester resin are reacted, and B is the total mass (g) of the raw material monomers constituting the polyester resin. The numbers in parentheses in the formula indicate the units of each value.)
[0018] The ester group concentration can be adjusted by the raw material monomer, and in the present invention, as described above, at least ethylene glycol and / or an α,ω-dicarboxylic acid compound having 4 carbon atoms is used.
[0019] Examples of the α,ω-dicarboxylic acid compound having 4 carbon atoms include fumaric acid, maleic acid, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0020] From the viewpoint of adjusting the ester group concentration, the content of ethylene glycol and / or an α,ω-dicarboxylic acid compound having 4 carbon atoms (the content of ethylene glycol or the α,ω-dicarboxylic acid compound having 4 carbon atoms, or the total content of both when both are used in combination) is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 43 mol % or more, and even more preferably 47 mol % or more, of the total amount of the alcohol component and the carboxylic acid component, and is 100 mol % or less, preferably 80 mol % or less, and more preferably 60 mol % or less.
[0021] Examples of the alcohol component other than ethylene glycol include aliphatic diols having 3 or more carbon atoms, preferably 6 to 12 carbon atoms, other than ethylene glycol, such as 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol; aromatic diols such as alkylene oxide adducts of bisphenol A; bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, and trimethylolpropane or higher alcohols.
[0022] Examples of carboxylic acid components other than α,ω-dicarboxylic acid compounds having 4 carbon atoms include adipic acid (number of carbon atoms: 6), suberic acid (number of carbon atoms: 8), azelaic acid (number of carbon atoms: 9), sebacic acid (number of carbon atoms: 10), dodecanedioic acid (number of carbon atoms: 12), tetradecanedioic acid (number of carbon atoms: 14), hexadecanedioic acid (number of carbon atoms: 16), aliphatic dicarboxylic acids such as succinic acid having an alkyl group or an alkenyl group on the side chain, aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid, trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0023] Furthermore, from the viewpoint of improving hydrophobicity, the alcohol component and / or the carboxylic acid component of the crystalline polyester resin preferably contains a monofunctional monomer.
[0024] From the viewpoint of improving hydrophobicity, the monofunctional monomer is preferably an aliphatic monoalcohol and / or an aliphatic monocarboxylic acid compound.
[0025] Examples of monofunctional monomers contained in the alcohol component include aliphatic monoalcohols such as capryl alcohol, capric alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol.
[0026] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monoalcohol is preferably 6 or more, more preferably 9 or more, even more preferably 10 or more, and even more preferably 12 or more, and from the viewpoint of low-temperature fixability, the carbon number is preferably 24 or less, more preferably 23 or less, and even more preferably 22 or less.
[0027] Examples of monofunctional monomers contained in the carboxylic acid component include aliphatic monocarboxylic acids such as caproic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and aliphatic monocarboxylic acid compounds such as alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.
[0028] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monocarboxylic acid compound is preferably 6 or more, more preferably 9 or more, and even more preferably 10 or more, and from the viewpoint of low-temperature fixability, it is preferably 24 or less, more preferably 23 or less, and even more preferably 22 or less. Here, when the aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.
[0029] The content of the monofunctional monomer in the total amount of the alcohol component and the carboxylic acid component is preferably 2 mol % or more, more preferably 3 mol % or more, and from the viewpoint of storage stability, is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 15 mol % or less.
[0030] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol component and the carboxylic acid component.
[0031] The equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.8 or more, more preferably 0.9 or more, from the viewpoint of adjusting the softening point of the polyester resin, and is preferably 1.2 or less, more preferably 1.1 or less, from the viewpoint of low-temperature fixability.
[0032] The crystalline polyester resin C can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and further, if necessary, in the presence of a co-catalyst, a polymerization inhibitor, etc., at a temperature preferably of 120°C or higher and 230°C or lower.
[0033] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropoxybis(triethanolaminate). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and preferably 1.5 parts by mass or less, and more preferably 1 part by mass or less, relative to 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the co-catalyst for the esterification catalyst include gallic acid. The amount of the co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, and more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0034] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.
[0035] The softening point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher from the viewpoint of storage stability, and is preferably 120°C or lower, and more preferably 110°C or lower from the viewpoint of low-temperature fixability.
[0036] From the viewpoint of storage stability, the melting point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher, and from the viewpoint of low-temperature fixability, it is preferably 120°C or lower, and more preferably 110°C or lower.
[0037] From the viewpoint of charging stability, the acid value of the crystalline polyester resin C is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, and preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less.
[0038] The content of crystalline polyester resin C in the total amount of crystalline polyester resin C and amorphous polyester resin A is preferably 2 mass % or more, more preferably 3 mass % or more, and even more preferably 5 mass % or more from the viewpoint of low-temperature fixability, and is preferably 40 mass % or less, more preferably 25 mass % or less, and even more preferably 15 mass % or less from the viewpoint of storage stability.
[0039] The amorphous polyester resin A is preferably an amorphous polyester resin or an amorphous composite resin in which a polyester resin is bonded to a styrene resin.
[0040] As the amorphous polyester resin, a polycondensation product of an alcohol component containing an alkylene oxide adduct of bisphenol A and a carboxylic acid component is preferable.
[0041] Examples of the alkylene oxide adduct of bisphenol A include those represented by the formula (I):
[0042] [ka]
[0043] (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added, each of which is a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) Preferred is a compound represented by the following formula:
[0044] From the viewpoint of low-temperature fixing ability, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 100 mol %.
[0045] Examples of other alcohol components include aliphatic diols, diols such as bisphenol A and hydrogenated bisphenol A, and trihydric or higher alcohols such as sorbitol, pentaerythritol, glycerin, and trimethylolpropane.
[0046] Examples of the carboxylic acid component include aromatic dicarboxylic acid compounds, aliphatic dicarboxylic acid compounds, and trivalent or higher carboxylic acid compounds.
[0047] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0048] Examples of the aliphatic dicarboxylic acid compound include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with a hydrocarbon group, glutaric acid, adipic acid, sebacic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0049] Examples of the trivalent or higher carboxylic acid compound include trimellitic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0050] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.
[0051] From the viewpoint of adjusting the softening point of the polyester resin, the equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0052] The polycondensation reaction conditions of the alcohol component and the carboxylic acid component of the amorphous polyester resin are similar to those of the crystalline polyester resin, except that the suitable reaction temperature is 160°C or more, more preferably 180°C or more, and 250°C or less, more preferably 240°C or less.
[0053] The polyester resin in the composite resin is similar to the amorphous polyester resin described above, and the styrene-based resin is an addition polymerization product of raw material monomers containing at least styrene or a styrene derivative such as α-methylstyrene or vinyltoluene (hereinafter, styrene and styrene derivatives are collectively referred to as "styrene compounds").
[0054] The content of the styrene compound, preferably styrene, in the raw material monomer of the styrene-based resin is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more from the viewpoint of storage stability, and is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 90% by mass or less from the viewpoint of low-temperature fixability.
[0055] The styrene-based resin may also contain, as a raw material monomer, an alkyl (meth)acrylate ester having an alkyl group with 7 or more carbon atoms. Examples of the alkyl (meth)acrylate ester include 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, and (iso)stearyl (meth)acrylate. It is preferable to use one or more of these. In this specification, "(iso)" means that both the case where this group is present and the case where it is not present are included, and when these groups are not present, it indicates that it is normal. Furthermore, "(meth)acrylic acid" refers to acrylic acid, methacrylic acid, or both.
[0056] From the viewpoint of improving the low-temperature fixing property of the toner, the number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester as a raw material monomer of the styrene-based resin is preferably 7 or more, more preferably 8 or more, and preferably 18 or less, more preferably 12 or less. The number of carbon atoms in the alkyl ester refers to the number of carbon atoms derived from the alcohol component constituting the ester.
[0057] The raw material monomers for the styrene-based resin may include raw material monomers other than styrene compounds and (meth)acrylic acid alkyl esters, for example, ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; ethylenic monocarboxylates such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone.
[0058] The addition polymerization reaction of raw material monomers for the styrene-based resin can be carried out by a conventional method in the presence of a polymerization initiator such as dibutyl peroxide or dicumyl peroxide, a chain transfer agent, a crosslinking agent, or the like, in the presence of an organic solvent or without a solvent. The temperature conditions are preferably 110° C. or higher, more preferably 140° C. or higher, and preferably 200° C. or lower, more preferably 170° C. or lower.
[0059] When an organic solvent is used in the addition polymerization reaction, xylene, toluene, methyl ethyl ketone, acetone, etc. can be used. The amount of the organic solvent used is preferably 10 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the raw material monomer of the styrene-based resin.
[0060] The composite resin is preferably a resin in which a polyester resin and a styrene-based resin are bonded together, and more preferably a resin in which a polyester resin and a styrene-based resin are chemically bonded together via a bireactive monomer that can react with both the raw material monomers of the polyester resin and the raw material monomers of the styrene-based resin.
[0061] The bireactive monomer is preferably a compound having at least one functional group selected from the group consisting of hydroxyl group, carboxyl group, epoxy group, primary amino group and secondary amino group, preferably hydroxyl group and / or carboxyl group, more preferably carboxyl group and ethylenically unsaturated bond in the molecule, more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, fumaric acid, maleic acid and maleic anhydride, and from the viewpoint of reactivity of polycondensation reaction and addition polymerization reaction, still more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid and fumaric acid. However, when used together with a polymerization inhibitor, a polyvalent carboxylic acid compound having an ethylenically unsaturated bond such as fumaric acid functions as a raw material monomer of polyester resin. In this case, fumaric acid etc. is not a bireactive monomer but a raw material monomer of polyester resin.
[0062] The amount of the bireactive monomer used is preferably 1 mol or more, more preferably 2 mol or more, relative to 100 mol of the total of the alcohol components of the polyester resin, from the viewpoint of increasing the dispersibility of the styrene resin and the polyester resin and improving the dispersibility of the raw materials in the toner, and is preferably 30 mol or less, more preferably 20 mol or less, and even more preferably 10 mol or less, from the viewpoint of improving the low-temperature fixing property of the toner.
[0063] Specifically, the composite resin is preferably produced by the following method: When a bireactive monomer is used, the bireactive monomer is preferably used together with a raw material monomer of a styrene-based resin from the viewpoint of improving the dispersibility of the raw material in the toner and the low-temperature fixability of the toner.
[0064] (i) A method in which a step (A) of polycondensation reaction using raw material monomers for a polyester resin is followed by a step (B) of addition polymerization reaction using raw material monomers for a styrene-based resin. In this method, step (A) is carried out under reaction temperature conditions suitable for polycondensation reaction, and the reaction temperature is lowered to carry out step (B) under temperature conditions suitable for addition polymerization reaction. It is preferable that the raw material monomer of the styrene-based resin is added to the reaction system at a temperature suitable for addition polymerization reaction. When a bireactive monomer is used together with the raw material monomer of the styrene-based resin, the bireactive monomer undergoes addition polymerization reaction and also reacts with the polyester resin. After step (B), the reaction temperature is increased again, and if necessary, a raw material monomer of a polyester resin having a valence of 3 or more and serving as a crosslinking agent is added to the polymerization system, so that the polycondensation reaction of step (A) and the reaction with the bireactive monomer can be further promoted.
[0065] (ii) A method in which step (B) of an addition polymerization reaction using raw material monomers for a styrene-based resin is followed by step (A) of a polycondensation reaction using raw material monomers for a polyester resin. In this method, step (B) is carried out under reaction temperature conditions suitable for addition polymerization reaction, and the reaction temperature is then raised to carry out the polycondensation reaction in step (A) under temperature conditions suitable for polycondensation reaction. When a bireactive monomer is used together with the raw material monomer of the styrene-based resin, the bireactive monomer is involved in both the addition polymerization reaction and the polycondensation reaction. The raw material monomers of the polyester resin may be present in the reaction system during the addition polymerization reaction, or may be added to the reaction system under temperature conditions suitable for the polycondensation reaction. In the former case, the progress of the polycondensation reaction can be controlled by adding an esterification catalyst at a temperature suitable for the polycondensation reaction.
[0066] (iii) A method in which the step (A) of polycondensation reaction of raw material monomers for polyester resin and the step (B) of addition polymerization reaction of raw material monomers for styrene-based resin are carried out under conditions in which they proceed in parallel. In this method, it is preferable to carry out step (A) and step (B) in parallel under reaction temperature conditions suitable for addition polymerization reaction, raise the reaction temperature, add a raw material monomer of a polyester resin having three or more valences as a crosslinking agent to the polymerization system as necessary under temperature conditions suitable for polycondensation reaction, and further carry out the polycondensation reaction of step (A). In this case, under temperature conditions suitable for polycondensation reaction, a polymerization inhibitor can be added to proceed with only the polycondensation reaction. When a bireactive monomer is used, the bireactive monomer is involved in both the addition polymerization reaction and the polycondensation reaction.
[0067] In the above method (i), a prepolymerized polyester resin may be used instead of the step (A) in which a polycondensation reaction is carried out. In the above method (iii), when the reaction is carried out under conditions in which the steps (A) and (B) proceed in parallel, a mixture containing raw material monomers for the styrene-based resin may be dropped into a mixture containing raw material monomers for the polyester resin to carry out the reaction.
[0068] The above methods (i) to (iii) are preferably carried out in the same container.
[0069] The mass ratio of the polyester resin to the styrene-based resin in the composite resin (polyester resin / styrene-based resin) is preferably 98 / 2 or less, more preferably 95 / 5 or less, and even more preferably 90 / 10 or less from the viewpoint of improving the dispersibility of the raw materials in the toner, and is preferably 60 / 40 or more, more preferably 70 / 30 or more, and even more preferably 75 / 25 or more from the viewpoint of low-temperature fixability. In the above calculation, the mass of the polyester resin is the amount obtained by subtracting the amount of reaction water dehydrated by the polycondensation reaction (calculated value) from the mass of the raw material monomers of the polyester resin used, and the amount of the bireactive monomer is included in the amount of raw material monomers of the polyester resin. The amount of the styrene-based resin is the total amount of the raw material monomers of the styrene-based resin.
[0070] The softening point of the amorphous polyester resin A is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher from the viewpoint of charging stability, and is preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 155°C or lower from the viewpoint of low-temperature fixability.
[0071] From the viewpoints of low-temperature fixability and fixing width, the amorphous polyester resin A may be composed of resins having different softening points. The difference in softening point between the two resins is preferably 10° C. or more, more preferably 20° C. or more, and is preferably 60° C. or less, more preferably 50° C. or less.
[0072] The softening point of the amorphous polyester resin having a higher softening point (resin AH) is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher, from the viewpoint of fixing width, and is preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 155°C or lower, from the viewpoint of low-temperature fixing ability.
[0073] Furthermore, the softening point of the amorphous polyester resin (resin AL) having the lower softening point is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, from the viewpoint of charging stability, and is preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower, from the viewpoint of low-temperature fixing ability.
[0074] The mass ratio of resin AH to resin AL (resin AH / resin AL) is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 75 / 25 or less.
[0075] The glass transition temperature of the amorphous polyester resin A is preferably 40° C. or higher, more preferably 50° C. or higher, from the viewpoint of storage stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, from the viewpoint of low-temperature fixability.
[0076] From the viewpoint of charging stability, the acid value of the amorphous polyester resin A is preferably 10 mgKOH / g or more, more preferably 15 mgKOH / g or more, and from the viewpoint of affinity with the crystalline polyester resin C, it is preferably 40 mgKOH / g or less, more preferably 35 mgKOH / g or less.
[0077] The content of the amorphous polyester resin A in the total amount of the crystalline polyester resin C and the amorphous polyester resin A is, from the viewpoint of charging stability, preferably 60% by mass or more, more preferably 75% by mass or more, even more preferably 85% by mass or more, and is preferably 98% by mass or less, more preferably 97% by mass or less, even more preferably 95% by mass or less.
[0078] From the viewpoint of durability, the mass ratio of the amorphous polyester resin A to the crystalline polyester resin C (amorphous polyester resin A / crystalline polyester resin C) is preferably 60 / 40 or more, more preferably 75 / 25 or more, even more preferably 85 / 15 or more, and is preferably 98 / 2 or less, more preferably 97 / 3 or less, even more preferably 95 / 5 or less.
[0079] In the toner, the crystalline polyester resin C and the amorphous polyester resin A are contained as binder resins.
[0080] Other examples of the binder resin include vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.
[0081] The total content of the crystalline polyester resin C and the amorphous polyester resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0082] In addition, the content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 95% by mass or less.
[0083] The release agent contains two types of ester waxes.
[0084] Ester waxes can be broadly divided into natural ester waxes and synthetic ester waxes.
[0085] Examples of natural ester waxes include carnauba wax, candelilla wax, rice wax, Japan wax, and jojoba wax.
[0086] The synthetic ester wax may be a product obtained by synthesis by condensing a carboxylic acid such as a fatty acid with an alcohol such as an aliphatic alcohol, or may be a commercially available product. In the present invention, examples of commercially available synthetic ester waxes that can be suitably used include "WEP-3" (manufactured by NOF Corp., melting point: 67°C), "WE-10" (manufactured by NOF Corp., melting point: 70°C), "WE-14" (manufactured by NOF Corp., melting point: 79°C), and "WEP-8" (manufactured by NOF Corp., melting point: 80°C).
[0087] In the present invention, carnauba wax is preferred from the viewpoint of durability, and synthetic ester wax is preferred from the viewpoint of smear resistance.
[0088] The content of carnauba wax in the release agent is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 65% by mass or more, even more preferably 80% by mass or more, and is preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less.
[0089] The content of the synthetic ester wax in the release agent is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 35% by mass or less, even more preferably 20% by mass or less.
[0090] Therefore, the two types of ester waxes are preferably carnauba wax and synthetic ester wax. The mass ratio of carnauba wax to synthetic ester wax (carnauba wax / synthetic ester wax) is preferably 40 / 60 or more, more preferably 50 / 50 or more, even more preferably 65 / 35 or more, even more preferably 80 / 20 or more, and is preferably 99 / 1 or less, more preferably 95 / 5 or less, even more preferably 90 / 10 or less.
[0091] The melting point of carnauba wax is around 83° C., and from the viewpoint of low-temperature fixability, it is preferable that the synthetic ester wax used in combination with carnauba wax has a melting point lower than that of carnauba wax.
[0092] The melting point of the synthetic ester wax is preferably 50°C or higher, more preferably 55°C or higher, and even more preferably 60°C or higher, and is preferably 80°C or lower, more preferably 75°C or lower, and even more preferably 70°C or lower.
[0093] In the present invention, as described above, both the durability of the toner and the smear resistance of the printed matter can be achieved without excessively increasing the amount of the release agent, and therefore the total content of the two types of ester waxes is 1 part by mass or more, preferably 1.5 parts by mass or more, more preferably 2.5 parts by mass or more, and 10 parts by mass or less, preferably 8 parts by mass or less, more preferably 6 parts by mass or less, per 100 parts by mass of the total amount of the crystalline polyester resin C and the amorphous polyester resin A.
[0094] The total content of the two types of ester waxes in the release agent is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0095] The toner of the present invention may contain a release agent other than the ester wax within a range that does not impair the effects of the present invention. Examples of other release agents include hydrocarbon waxes such as polypropylene wax, polyethylene wax, ethylene-propylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts.
[0096] The toner of the present invention may contain additives such as a colorant, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver, in addition to the binder resin containing the crystalline polyester resin C and the amorphous polyester resin A and the release agent.
[0097] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.
[0098] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0099] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.
[0100] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).
[0101] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.
[0102] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0103] The toner of the present invention may be a toner obtained by any of the known methods such as a melt kneading method, an emulsion aggregation method, a polymerization method, etc., but from the viewpoint of productivity and dispersibility of the colorant, a pulverized toner by a melt kneading method is preferred. In the case of a pulverized toner by a melt kneading method, for example, raw materials such as a binder resin, a release agent, a colorant, a charge control agent, etc. are uniformly mixed in a mixer such as a Henschel mixer, and then melt kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll type kneader, etc., and cooled, pulverized, and classified to produce the toner.
[0104] In the toner of the present invention, it is preferable to use an external additive in order to improve transferability. Examples of the external additive include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferable, and from the viewpoint of the transferability of the toner, hydrophobic silica that has been hydrophobized is more preferable.
[0105] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.
[0106] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.
[0107] The external addition treatment by mixing the toner particles with the external additives can be carried out according to a conventional method, and a mixer such as a Henschel mixer can be used.
[0108] From the viewpoint of the electrostatic chargeability, fluidity, and transferability of the toner, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles before being treated with the external additive, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.
[0109] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.
[0110] The toner of the present invention can be used as it is as a toner for one-component development, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively. EXAMPLES
[0111] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.
[0112] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.
[0113] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintain at 0°C for 1 minute. Then, measure at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature. For crystalline resins, the maximum endothermic peak temperature is regarded as the melting point.
[0114] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and cooled from that temperature at a rate of 10°C / min to 0°C. Next, the sample is heated at a rate of 10°C / min, and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.
[0115] [Acid value of resin] Measurements are performed based on the method of JIS K 0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K 0070 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)) for amorphous resins, and to a mixture of chloroform and dimethylformamide (chloroform:dimethylformamide = 7:3 (volume ratio)) for crystalline resins.
[0116] [Melting point of release agent] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C at a heating rate of 10°C / min, and cooled to -10°C at a heating rate of 5°C / min. The sample is then heated to 180°C at a heating rate of 10°C / min and measured, and the maximum endothermic peak temperature is taken as the melting point.
[0117] [Volume Median Particle Size and CV Value of Resin Particles, Colorant Particles, and Release Agent Particles] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba, Ltd.) (2) Measurement conditions: Put the sample dispersion in a measurement cell, add distilled water, and measure the volume median particle size (D 50 ) is measured.
[0118] [Solid Content Concentration of Resin Dispersion, Colorant Dispersion, and Release Agent Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), 5 g of the measurement sample is dried at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, fluctuation range 0.05%), and the moisture content (mass%) of the dispersion is measured. The solid content concentration is calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0119] [Volume Median Particle Size of Agglomerated Particles] Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size (D 50 ) is required.
[0120] [Circularity of Toner Particles] The circularity of the toner particles is measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of toner particles is prepared by diluting it with deionized water so that the solid content concentration becomes 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0121] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.
[0122] [Volume median particle size of toner (D 50 )〕 Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer III (registered trademark) version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is required.
[0123] Resin manufacturing example 1 The alcohol component, fumaric acid, esterification catalyst, and polymerization inhibitor shown in Table 1 were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 230°C in a mantle heater under a nitrogen atmosphere, and polycondensation was carried out for 7 hours. Thereafter, the temperature was lowered to 200°C, trimellitic anhydride was added, and the temperature was raised to 210°C to carry out a polycondensation reaction, and the reaction was continued until the softening point reached the temperature shown in Table 1, to obtain an amorphous polyester resin (resin A1).
[0124] Resin manufacturing example 2 The alcohol components shown in Table 1, carboxylic acid components other than trimellitic anhydride, and an esterification catalyst were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 230°C in a mantle heater under a nitrogen atmosphere, and polycondensation was carried out for 7 hours. The temperature was then lowered to 200°C, trimellitic anhydride was added, and the temperature was raised to 210°C to carry out a polycondensation reaction, and the reaction was continued until the softening point reached the temperature shown in Table 1, to obtain an amorphous polyester resin (resin A2).
[0125] [Table 1]
[0126] Resin manufacturing example 3 The raw material monomers and esterification catalysts of polyester resins other than trimellitic anhydride shown in Table 2 were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the mixture was heated to 160 ° C in a mantle heater under a nitrogen atmosphere, and then the raw material monomers of the styrene resin, the bireactive monomer, and the polymerization initiator were dropped over 1 hour to perform polymerization. The temperature was raised to 200 ° C and the reaction was allowed to mature for 1 hour to generate a styrene resin in the reaction system, and then the temperature was raised to 230 ° C over 1 hour to confirm that all the solid monomers had melted and reacted. After that, the pressure was reduced to 8 kPa and the mixture was dehydrated and condensed for 1 hour, and then the temperature was lowered to 210 ° C, trimellitic anhydride was added, and the reaction was allowed to continue for another 1 hour. The pressure was reduced to 8 kPa, and the reaction was allowed to continue until the softening point reached the temperature shown in Table 2, to obtain an amorphous composite resin (resin B1).
[0127] [Table 2]
[0128] Resin manufacturing example 4 The alcohol component and carboxylic acid component shown in Table 3 were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 200°C over 8 hours in a mantle heater under a nitrogen atmosphere. Then, an esterification catalyst was added, and the reaction was carried out at 8.0 kPa until the softening point reached the temperature shown in Table 3, obtaining crystalline polyester resins (resins C1 to C4, C7 to C9).
[0129] Resin manufacturing example 5 The alcohol component, carboxylic acid component, and polymerization inhibitor shown in Table 3 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. Then, an esterification catalyst was added, and the reaction was carried out at 8.0 kPa until the softening point reached the temperature shown in Table 3, obtaining crystalline polyester resins (resins C5 and C6).
[0130] [Table 3]
[0131] Examples 1 to 16 and Comparative Examples 1 to 8 The binder resin and release agent shown in Tables 4 and 5, 4 parts by mass of colorant "Mogul-L" (Cabot Corporation, carbon black), 0.2 parts by mass of colorant "ECB-301" (Dainichiseika Color & Chemicals Mfg. Co., Ltd., phthalocyanine blue), and 1 part by mass of charge control agent "T-77" (Hodogaya Chemical Co., Ltd.) were thoroughly stirred with a Henschel mixer, and then melt-kneaded using a co-rotating twin-screw extruder "PCM-30" (Ikegai Corporation). The operating conditions of the co-rotating twin-screw extruder were barrel set temperature 100°C, shaft rotation speed 200r / min (shaft rotation peripheral speed 0.30m / sec), and mixture supply rate 10kg / h. The resulting kneaded product was cooled and the volume median particle size (D 50 The particles were pulverized and classified so that the particle size became 7.0 μm, thereby obtaining toner particles.
[0132] To 100 parts by mass of the obtained toner particles, 1.2 parts by mass of "Aerosil R-972" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.4 parts by mass of "RY-50" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) were added as external additives, and the mixture was mixed in a Henschel mixer at 2300 r / min for 3 minutes to perform external additive treatment and obtain a toner.
[0133] The release agents used in the examples and comparative examples are as follows: W1: "WAX-C1" (Kato Yoko Co., Ltd.), carnauba wax, melting point 83℃ W2: "WE-10" (NOF Corp.), synthetic ester wax, melting point 67°C W3: "WEP-3" (NOF Corp.), synthetic ester wax, melting point 70°C W4: "HNP-9" (manufactured by Nippon Seiro Co., Ltd.), paraffin wax, melting point 77°C
[0134] Example 17 A toner was obtained in the same manner as in Example 1, except that the melt-kneading was performed using a continuous two-roll open-roll kneader "Kneedex" (manufactured by Nippon Coke & Engineering Co., Ltd.) instead of the same-rotation twin-screw extruder. The continuous two-roll open-roll kneader had an outer diameter of 0.14 m and an effective roll length of 0.8 m, and the operating conditions were a rotation speed of the high-rotation roll (front roll) of 75 r / min (circumferential speed 33 m / min), a rotation speed of the low-rotation roll (rear roll) of 50 r / min (circumferential speed 22 m / min), and a roll gap of 0.1 mm. The heating and cooling medium temperatures in the rolls were set as follows: the temperature of the raw material input side of the high-rotation roll was set to 140°C, and the temperature of the kneaded material discharge side was set to 110°C, and the temperature of the raw material input side of the low-rotation roll was set to 65°C, and the temperature of the kneaded material discharge side was set to 30°C. The supply speed of the raw material mixture was 10 kg / h, and the average residence time was about 5 minutes.
[0135] Example 18 <Preparation of resin dispersion> In a 3-liter vessel equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, 140 g (70 parts by mass) of resin A2, 50 g (25 parts by mass) of resin B1, 10 g (5 parts by mass) of resin C3, and 200 g of methyl ethyl ketone were placed and dissolved for 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700g of deionized water was added over 50 minutes while stirring at 200r / min to cause phase inversion emulsification. The obtained solution was maintained at 73°C, and methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. Thereafter, while continuing to stir, the dispersion was cooled to 30°C, and deionized water was added so that the solid content concentration was 20% by mass, to obtain a resin dispersion.
[0136] <Preparation of Colorant Dispersion> In a 1-liter beaker, 116.2 g of colorant "Mogul-L" (carbon black, manufactured by Cabot Corporation), 5.81 g of colorant "ECB-301" (manufactured by Dainichiseika Color & Chemicals Co., Ltd.), 154.9 g of anionic surfactant "Neopelex (registered trademark) G-15" (manufactured by Kao Corporation, 15% by mass aqueous solution of sodium dodecylbenzenesulfonate), and 260 g of deionized water were mixed and dispersed using a homogenizer at room temperature for 3 hours, and then deionized water was added so that the solids concentration became 20% by mass, thereby obtaining a colorant dispersion. The volume median particle diameter (D 50 ) was 118 nm.
[0137] <Preparation of release agent dispersion> 42 g of release agent "W1" (WAX-C1, manufactured by Kato Yoko Co., Ltd., carnauba wax, melting point 83°C), 8 g of release agent "W2" (WE-10, manufactured by NOF Corp., synthetic ester wax, melting point 67°C), 5 g of cationic surfactant (manufactured by Kao Corp., trade name: Sanisol B50) and 200 g of deionized water were heated to 95°C and the release agent was dispersed using a homogenizer, and then dispersed using a pressure discharge homogenizer, and deionized water was added to obtain a release agent dispersion liquid with a solid content concentration of 20 mass%. The volume median particle diameter (D 50 ) was 550 nm.
[0138] <Toner Preparation> Into a 3-liter four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 549 g of the resin dispersion, 23 g of the colorant dispersion, 16.5 g of the release agent dispersion, and 3.3 g of a 15% by mass aqueous solution of sodium dodecylbenzenesulfonate "Neopelex G-15" (Kao Corporation, an anionic surfactant) were placed and mixed at a temperature of 25° C. Next, while stirring the resulting mixture, a solution obtained by dissolving 43 g of ammonium sulfate in 980 g of deionized water and adding a 4.8% by mass aqueous solution of potassium hydroxide to adjust the pH to 8.2 was added dropwise over 10 minutes at 25° C., and the temperature was then raised to 58° C. over 2 hours to measure the volume median particle diameter (D 50 The temperature was maintained at 58° C. until the particle diameter reached 7.0 μm, to obtain a dispersion of aggregated particles.
[0139] To the obtained dispersion of aggregated particles, 22 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (Kao Corporation, anionic surfactant, effective concentration 27% by mass) and 1100 g of deionized water were added. The temperature was then raised to 75°C over 1 hour, and the temperature was maintained at 75°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which the aggregated particles were fused together.
[0140] The obtained dispersion of fused particles was cooled to 30°C, and the dispersion was subjected to suction filtration to separate the solid content, which was then washed with deionized water at 25°C and suction filtered at 25°C for 2 hours. Thereafter, the solid content was vacuum dried at 33°C for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC) to determine the volume median particle diameter (D 50 ) yielded 7.0 μm toner particles.
[0141] To 100 parts by mass of the obtained toner particles, 1.2 parts by mass of "Aerosil R-972" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.4 parts by mass of "RY-50" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) were added as external additives, and the mixture was mixed in a Henschel mixer at 2300 r / min for 3 minutes to perform external additive treatment and obtain a toner.
[0142] Test Example 1 [Smear of printed matter] The toner was loaded into a copier "AR-505" (product name, manufactured by Sharp Corporation), and a solid image was removed before passing through the fixing machine to obtain a printout in an unfixed state (printed area: 2 cm × 12 cm, adhesion amount: 0.5 mg / cm 2 In addition, unfused images were printed twice on the same paper, with the adhesion amount reaching 1.5 mg / cm 2 The unfixed image thus obtained was fixed at 150° C. and 300 mm / s to obtain a print. A stainless steel weight measuring 3 cm in length, 3 cm in width, and 6.5 cm in height, and weighing 500 g, was placed on the resulting print and moved back and forth over the print at a speed of 0.5 m / s. One back and forth was counted as one pass, with a maximum of 50 passes. The non-printed areas were visually checked for the presence of black bands of toner adhesion, and smear resistance was evaluated based on the number of passes until this occurred. The results are shown in Tables 4 and 5. A higher number of passes indicates better smear resistance. In the tables, ">50" indicates that no toner adhesion was observed even after 50 passes.
[0143] Test Example 2 [Durability] The toner was loaded into a non-magnetic single-component developing device, Monochrome LED Printer B432dnw (manufactured by Oki Electric Industry Co., Ltd.), and a printing durability test was conducted at a print rate of 0.3% in an environment of 35°C / relative humidity of 50%. A solid image was printed every hour, and durability was evaluated by visual inspection to see if there were any white streaks caused by blade filming. The test was stopped when the occurrence of white streaks was confirmed, and was continued for up to 18 hours. The results are shown in Tables 4 and 5. In the tables, ">18" means that no white streaks had occurred even after 18 hours. The higher the number, the better the durability.
[0144] [Table 4]
[0145] [Table 5]
[0146] From the above results, it is apparent that, in comparison with Comparative Examples 1 to 8, the toners of Examples 1 to 18 have achieved both durability and smear resistance. [Industrial Applicability]
[0147] The toner for developing electrostatic images of the present invention is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.
Claims
1. The toner for developing electrostatic images contains a crystalline polyester resin C, an amorphous polyester resin A, and a release agent, the crystalline polyester resin C being a polycondensate of an alcohol component and a carboxylic acid component, the alcohol component containing ethylene glycol and / or the carboxylic acid component containing an α,ω-dicarboxylic acid compound having 4 carbon atoms, the crystalline polyester resin C having an ester group concentration of 5.5 mmol / g or more and 9.0 mmol / g or less, the release agent containing two types of ester waxes, the total content of the ester waxes being 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the total amount of the crystalline polyester resin C and the amorphous polyester resin A.
2. 2. The toner for developing electrostatic images according to claim 1, wherein one of the two kinds of ester waxes is carnauba wax.
3. 3. The toner for developing electrostatic images according to claim 2, wherein the content of the carnauba wax in the releasing agent is 50% by mass or more.
4. 2. The toner for developing electrostatic images according to claim 1, wherein one of the two kinds of ester waxes is a synthetic ester wax.
5. 2. The toner for developing electrostatic images according to claim 1, wherein the two kinds of ester waxes are carnauba wax and synthetic ester wax.
6. 6. The toner for developing electrostatic images according to claim 5, wherein a mass ratio of the carnauba wax to the synthetic ester wax is from 50 / 50 to 99 / 1.
7. 7. The toner for developing electrostatic images according to claim 1, wherein a mass ratio of the amorphous polyester resin A to the crystalline polyester resin C is 60 / 40 or more and 98 / 2 or less.
Citation Information
Patent Citations
Toner for electrostatic charge image development
JP2013142712A
Toner
JP2014109704A
Toner for developing electrostatic latent image and manufacturing method therefor
WO2017179357A1